Analysis of spatial and temporal changes of wetland ecosystems in Xuan Thuy National Park (Nam Dinh province) based on techniques of remote sensing and GIS - Hai, Ho Thanh; Thanh Nhan, Hoang Thi; Tuan, Tran Anh (Academia Journal of Biology, 2015)
Xuan Thuy National Park and surrounding area located in estuary of the Red river (Ba Lat mouth) with characterized ecosystem of mangroves on the tidal delta (the largest delta in the north of Vietnam). Based on analysis satellite images collected in various periods and GIS techniques, maps of wetland ecosystem types of the Xuan Thuy national park in years of 1986, 1995, 2007 and 2013 that were established. Areas of each wetland types in each of above periods were calculated. Spatial and temporal changes of these wetland ecosystems were studied also. Study results show that wetland ecosystems, especially mangrove forest were changed on morphology, areas, and spatial distribution under influent of natural evolution and anthropogenic impacts. Based on succession of mangrove forest related to formation of soil, ecological succession of coastal wetlands in Xuan Thuy national park are occurred according to direction from continent to the sea such as: Settlement and rice field -> Sedge field/shrimp pond -> Mangrove forest -> Estuary sandy bar. Therefore, it is necessary to establish of models for sustainable use of estuary coastal wetlands that are available to each periods of ecological succession.